gamma-Tubulin in Arabidopsis: gene sequence, immunoblot, and immunofluorescence studies. - Liu, B (1994)
gamma-Tubulin is a protein associated with microtubule (Mt)-organizing centers in a variety of eukaryotic cells. Unfortunately, little is known about such centers in plants. Genomic and partial cDNA clones encoding two gamma-tubulins of Arabidopsis were isolated and sequenced. Comparisons of genomic and cDNA sequences showed that both genes, TubG1 and TubG2, contain nine introns at conserved locations. The sequences of the two genes both predict proteins containing 474 amino acids, with molecular masses of 53,250 and 53,280 D, respectively. The predicted gamma 1- and gamma 2-tubulins exhibit 98% amino acid identity with each other and approximately 70% amino acid identity with the gamma-tubulins of animals and fungi. RNA gel blot results demonstrated that both genes are transcribed in suspension culture cells, seedlings, and roots and flowers of mature plants. Immunoblots of Arabidopsis proteins using an antibody specific to a conserved peptide of gamma-tubulin showed a major cross-reacting polypeptide with an M(r) of 58,000. The same antibody stained all Mt arrays in tissue and suspension culture cells of this species. Binding was inhibited by the homologous oligopeptide in the gamma-tubulins predicted by the two Arabidopsis gene sequences. Antibody staining avoided the plus ends of Mts at the kinetochores and cell plate, but unlike the case in animal cells, seemed to be localized over broad stretches of the kinetochore fibers and phragmoplast toward the minus ends. We concluded that at least two gamma-tubulin protein homologs are present in Arabidopsis and that at least one of them is localized along Mt arrays. Its distribution is correlated with and may help explain unique characteristics of Mt organization in plants.